Prevulcanization of isoprene rubber latex - Sae-heng, Kewwarin; Iso, Noriaki; Kosugi, Kenichiro; Kawahara, Seiichi (Colloid and polymer science, 2015)
Prevulcanization of isoprene rubber (IR) latex was investigated by latex-state 13 C-NMR spectroscopy to understand its mechanism in latex stage. The prevulcanization was carried out at 50 to 90 °C with sulfur (S) and zinc-dibutyldithiocarbamate (ZDBC) as vulcanizing agents. The prevulcanized IR latex was subjected to latex-state 13 C-NMR spectroscopy. The signal at 44 ppm was assigned to secondary carbons adjacent to carbons linking to S atoms, whereas the signal at 58 ppm was assigned to tertiary and quaternary carbons linking to S atoms. The time evolution of the small signals at 44 and 58 ppm was investigated at various temperatures, and kinetic constants were determined at each temperature. The activation energy of the prevulcanization of IR latex was estimated from the kinetic constants to be about 80 kJ/mol.